Development of wage dispersion: A case study of Hong Kong - Ho Ching Florence Yuen (International Labour Organization (ILO), 2017)
In recent decades, economic performance of Hong Kong has been remarkable and currently its per capita income is amongst the highest in the world. Meanwhile, its income distribution is highly uneven compare to the major advanced economies. As employment income remains the largest constituent of household market income in Hong Kong, it is expected that the development of its earning inequality may have contributed to the high income inequality. This paper aims to study how wage dispersion has been developed in Hong Kong since 1980s and to identify the reasons behind such development. It also intends to outline policies that can be implemented to reduce the wage dispersion in Hong Kong. Examination on relevant statistics reveals that wage inequality in Hong Kong has been rising since 1980s. Though market factors were definitely in play, growing wage gap was largely a result of insufficient labour market institutions to protect workers from employment practices aiming to enhance wage flexibility. While large scale institutional reform has low feasibility, initiatives to fine-tune the current institutional setting are essential to restore the balance of power between workers and employers in wage determination. Reforms on tax and social security system may also relief the impact of wage dispersion on growth and employment.
Keywords: 330